EVALUASI PROGRAM SEKOLAH BERBASIS MODEL CIPP DALAM MENGUATKAN KARAKTER PROFIL PELAJAR PANCASILA DI SEKOLAH DASAR - Sugiyanto; Rahayu, Anny; Muhibbin, Ahmad; Susilo, Agus (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to evaluate the strengthening program of the Profil Pelajar Pancasila (Pancasila Learner Profile) in elementary schools using the CIPP (Context, Input, Process, Product) evaluation model. The research employs a descriptive qualitative approach, with data collection techniques including observation, interviews, and documentation. The evaluation results indicate that the context and input components are in the